DEVELOPING PROFESSIONAL IDENTITY THROUGH LINKEDIN: IMPROVING CV WRITING AND INTERVIEW SKILLS AMONG BUSINESS ADMINISTRATION STUDENTS AT POLITEKNIK LP3I JAKARTA - Ali Satri Efendi; Retno Setya Budiasningrum; Tri Andriani (IC-BESTS: International Conference on Business, Economics, Technology, and Social Sciences, 2026)
This study aims to enhance students’ professional identity, CV writing, and job interview skills through LinkedIn profile management among Business Administration students at Politeknik LP3I Jakarta. The study involved 20 third-semester students and was conducted in two cycles consisting of planning, action, observation, and reflection. During the intervention, students were guided to create and optimize their LinkedIn profiles by presenting information related to their education, skills, achievements, experiences, and career aspirations. Data were collected through classroom observations, CV assessments, interview simulations, and reflective evaluations. The findings show that students improve their ability to organize and present professional information, resulting in more structured CVs. The interview simulations also reveal that students are able to provide more relevant responses that aligned with the information displayed on their LinkedIn profiles. The study concludes that integrating LinkedIn profile management into career preparation activities supports the development of employability skills and career readiness, particularly in CV writing and job interview preparation.